Motivation and Risk Behind Financial Statement Fraudulence Using Fraud Theory - Nico Alexander; Wijaya, Novia; Firnanti, Friska (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2025)
Financial information is a critical resource for users of financial statements in their decision-making processes. However, errors in decision-making can arise from management's fraudulent activities within these financial statements. Such actions primarily benefit management while adversely affecting other stakeholders. Consequently, this study explores the motivations behind management's engagement in fraudulent practices in financial reporting, utilising established fraud theories, including the triangle, diamond, pentagon, and hexagon models. The research focuses on cyclical and non-cyclical sector companies listed on the Indonesia Stock Exchange from 2020 to 2022, with a sample of 152 companies selected through purposive sampling. Logistic regression analysis is employed to test the hypotheses. The findings indicate that, according to each theoretical framework, the motivations for fraud stem from pressures to sustain the company's financial stability and the opportunities and collusion available to perpetrate such fraud.